Does immigration weaken natives' support for the welfare state? Evidence from Germany - Holger Stichnoth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Using data from the 1997 and 2002 waves of the German Socio-Economic Panel and from official statistics, I study whether natives are less supportive of state help for the unemployed in regions where the share of foreigners among the unemployed is high. Unlike previous studies, I use individual-level panel data, which allows a more convincing identification of a causal effect. I find that the negative bivariate association is mainly driven by observed individual differences such as East German origin or income. While there remains some evidence of a negative association even after adjusting for individual differences (including time-invariant unobserved differences), the association is weak compared to the association with other variables such as income, self-employment, or East German origin.
Keywords: H53; H55; I38; J15; J61; 330; redistribution; social security; welfare state; immigration; ethnic diversity; Germany; cluster-robust standard errors; two-way clustering; Einwanderung; Sozialstaat; Meinung; Bevölkerung; Schätzung; Deutschland